ADHERENCE TO TREATMENT AND QUALITY OF LIFE OF PATIENTS WITH CARDIOVASCULAR DISEASES AT THE OUTPATIENT TREATMENT STAGE OF MEDICAL CARE - E. A. Kuzheleva; V. A. Fedyunina; A. A. Garganeeva (Евразийский Кардиологический Журнал, 2020)
Aim: to analyze an adherence to treatment, factors affecting it, and the quality of life of patients with cardiovascular diseases at the outpatient stage of medical care.Material and methods. The population of the study was 225 people. The Moriski-green compliance scale was used to analyze patients’ adherence to treatment, and the EuroQol EQ-5D-5L international questionnaire was used to assess the quality of life of patients. Statistical data processing was performed using the program STATISTICA 10.0.Results. The percentage of committed to treating patients who sought outpatient care was 59%. The main reason for poor adherence was forgetfulness – 25,27 %. It is patient’s opinion, in 73.8% of cases, communication with a doctor plays an important role in improving their compliance. The total index of quality of life (QOL) of patients with cardiovascular diseases (CVD) was 0.712 ± 0.165. In estimating the relationship between quality of life and adherence to treatment, a positive correlation was found: the more compliant the patient, the higher their quality of life, and vice versa (r=0.2, p=0.013). The relationship between high adherence to treatment and quality of life was confirmed in the group of men (p=0.01), while the statistical significance of differences was not achieved in women (p=0.2). In examining the aspect of a disease of chronic heart failure (CHF), the worsening of NYHA functional class (from I to II) was accompanied by a sharp decrease in self-esteem of health for both sexes (p=0.01).Conclusion. Almost every second patient is against of the rules of the medication regimen. Better adherence to treatment can be facilitated by more careful attention from the attending physician with a detailed explanation of the causes and the aspect of the disease, treatment methods, as well as ways to self-control the symptoms of the disease. The degree of treatment adherence is correlated with the level of quality of life on the EQ-5D-5L scale, mainly in the male population.